Generation and evolution of diamondoids in source rock. (November 2015) - Fang, Chenchen; Xiong, Yongqiang; Li, Yun; Chen, Yuan; Tang, Youjun
Abstract: Thermal maturation-related variations in the abundance and distribution of diamondoids in source rocks were investigated by thermal simulation experiments on extracts and kerogen obtained from a same marine shale, and by quantitative analysis of diamondoids within pyrolysates using highly sensitive and selective gas chromatography–triple quadrupole mass spectrometry (GC–MS–MS). The results indicate that diamondoids within the marine shale are generated mainly during 0.8%–1.7% EasyRo, generally deriving from extractable organic matter within source rocks, and are destroyed after 1.7% EasyRo to be entirely removed by ca. 3.0% EasyRo. Ternary plots of the relative distribution of diamondoids and bivariate diagrams for diamondoid parameters (e.g., DMA/MD vs. DMAI-1, and DMA/MD vs. TMAI-1) show systematic changes in diamondoids with increasing thermal maturity (expressed as EasyRo). Highlights: Diamondoids in source rock are generated in maturity range of 0.8–1.7% EasyRo. Extract is the dominant contributor of diamondoids in source rock. Diamondoid indices can be used to evaluate the maturity of highly mature source rock.